2018
DOI: 10.21608/jabps.2018.5283.1023
|View full text |Cite
|
Sign up to set email alerts
|

Pyridazinones and pyrrolones as promising Scaffolds in Medicinal Chemistry

Abstract: Pyridazinones and pyrrolones are important building blocks for some important drugs such as the naturally occurring antibacterial pyrrolone, althiomycin; the cardiotonic pyridazinones, pimobendan and levosimendan and the analgesic anti-inflammatory, emorfozan. Therefore, researchers all over the world paid attention to prepare various pyridazinones and pyrroolones derivatives. The variability in the biological response and ease of preparation from the corresponding furanones attracted attention of researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…[38] The oxo derivative of pyridazine that is pyridazin-3(2H)-one scaffold (either saturated or unsaturated) is known as the "wonder nucleus" as it gives out diverse derivatives with all types of pharmacological activities, so it is a vital scaffold in drug discovery and development. [39][40][41][42] This study focuses on the development of pyridazinones as promising anti-inflammatory agents, covering the articles published from 1999 to 2021.…”
Section: Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] The oxo derivative of pyridazine that is pyridazin-3(2H)-one scaffold (either saturated or unsaturated) is known as the "wonder nucleus" as it gives out diverse derivatives with all types of pharmacological activities, so it is a vital scaffold in drug discovery and development. [39][40][41][42] This study focuses on the development of pyridazinones as promising anti-inflammatory agents, covering the articles published from 1999 to 2021.…”
Section: Inhibitionmentioning
confidence: 99%
“…The oxo derivative of pyridazine that is pyridazin‐3(2 H )‐one scaffold (either saturated or unsaturated) is known as the “wonder nucleus” as it gives out diverse derivatives with all types of pharmacological activities, so it is a vital scaffold in drug discovery and development. [ 39–42 ]…”
Section: Anti‐inflammatory Activity Of Pyridazinonesmentioning
confidence: 99%
“…[ 11 , 12 ] Several DHPs were found to possess antimicrobial activity, QS, and biofilm inhibitory activities [ 13 ] such as those reported by our group [ 14 , 15 , 16 ], including DHPs with a thioether [ 17 ] or a seleno-urea [ 18 ] moiety. In addition, the biological activities of DHP-related compounds were also studied by other research groups [ 19 , 20 , 21 , 22 ], including rubrolide derivatives, which showed antibacterial [ 23 ], anticancer [ 24 ], and herbicidal [ 25 ] activities. Moreover, a recent paper by Ma et al also reported the synthesis and anti-virulence activities of several furanones and aryl-substituted pyrrolidone derivatives as quorum sensing inhibitors [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quinoline derivatives also display excellent anticancer activities via different mechanisms of action, such as the inhibition of tyrosine kinase, alkylating agents, cell cycle arrest, angiogenesis inhibition, apoptosis induction, cell migration disruption, targeting Bcl-2, and inhibition of antimitotic tubulin polymerization [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] (see ESI †).…”
Section: Introductionmentioning
confidence: 99%